Face-on oriented thermolabile Boc-isoindigo/thiophenes small molecules: From synthesis to OFET performance. (January 2020) - Shaker, Mohamed; Park, Byoungwook; Lee, Seongyu; Lee, Kwanghee
Abstract: A new series of protected isoindigo (ID) based solution processable donor-acceptor type of small molecules was synthesized. Tert-butoxycarbonyl (t-Boc) substituted isoindigo is used as the acceptor unit and oligothiophene derivatives as the donor units. Thermal decarboxylation of small molecules films at 200 °C eliminated the t-Boc side groups. The cleavage of the protecting group formed a variety of N–H …. .O=C hydrogen bonding across the lactam structures of the isoindigo. The molecular orientation during the thermal decarboxylation of ID-Boc to ID-H was examined using X-ray diffraction and atomic force microscopy. The H-bonding formation and its impact on the optical, thermal, electrochemical and ambipolar behavior were investigated. Graphical abstract: Image 1 Highlights: H-bonding self-organized isoindigo based small molecules were synthesized and characterized. During thermal deprotection, the targeted materials showed face on orientation in the solid state. The hole mobility is dramatically a thousandfold increased after thermal deprotection.